2017
DOI: 10.1371/journal.ppat.1006626
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a C-type lectin’s coiled-coil domain to the Domeless receptor directly activates the JAK/STAT pathway in the shrimp immune response to bacterial infection

Abstract: C-type lectins (CTLs) are characterized by the presence of a C-type carbohydrate recognition domain (CTLD) that by recognizing microbial glycans, is responsible for their roles as pattern recognition receptors in the immune response to bacterial infection. In addition to the CTLD, however, some CTLs display additional domains that can carry out effector functions, such as the collagenous domain of the mannose-binding lectin. While in vertebrates, the mechanisms involved in these effector functions have been ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 65 publications
(81 reference statements)
3
76
0
Order By: Relevance
“…Fluorescence was visualized on a confocal laser scanning microscope (Leica TCS-SP5, Germany). We calculated the colocalization percentage of Dorsal with nucleus stained with hochest, using the ImageJ according to the previously described methods [ 51 , 102 ]. In brief, we opened the picture and chosen Image-Color-Split channels, while closed the no need channels, and then clicked Plugins-colocalization analysis-colocalization threshold-OK.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence was visualized on a confocal laser scanning microscope (Leica TCS-SP5, Germany). We calculated the colocalization percentage of Dorsal with nucleus stained with hochest, using the ImageJ according to the previously described methods [ 51 , 102 ]. In brief, we opened the picture and chosen Image-Color-Split channels, while closed the no need channels, and then clicked Plugins-colocalization analysis-colocalization threshold-OK.…”
Section: Methodsmentioning
confidence: 99%
“…The initial description of the function for PIAS proteins was as negative regulators of STATs ( 22 ). In our previous study, we showed that activation of the JAK/STAT pathway resulted in AMPs expression ( 21 ). To explore whether the antibacterial inhibition ability of Mj PIAS is caused by the negative regulation of STAT in shrimp, we detect the expression levels of four AMPs (ALF-A1, ALF-C1, ALF-C2, and CruI-1) that are regulated by the JAK/STAT pathway ( 21 ) in MjPIAS -knockdown shrimp followed by V. anguillarum injection.…”
Section: Resultsmentioning
confidence: 99%
“…V. anguillarum (2 × 10 8 cells) was injected into shrimp after knockdown of MjPIAS for 48 h. Hemocytes were collected 3 h post infection and spread on a glass slide. Immunocytochemistry was performed following a previously described method ( 20 ) with an anti-STAT antibody (prepared in our laboratory) and an anti-p-STAT antibody (Abcam, San Francisco, USA) ( 21 ). All glass slides were observed under a fluorescence microscope (Olympus BX51, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Four milliliters of hemolymph obtained from oysters were fixed with 4 ml of a mixture 161 containing 2 ml of anticoagulant (pH 7.4) and 2 ml of 4% paraformaldehyde (Sun et al, 2017). 162…”
Section: Immunocytochemical Assay 160mentioning
confidence: 99%